2022
DOI: 10.1037/xhp0001006
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of central and peripheral processes in typing and handwriting: A direct comparison.

Abstract: This study aimed to investigate the interaction between linguistic and peripheral-motor processes in written production. Past research has focused on this topic by analyzing how handwriting and, more recently, typing execution were influenced by lexical and sublexical variables. We took a step further in this study by directly comparing handwriting and typing, examining if different motor executions allow for different flows of linguistic processing. Participants typed and handwrote a set of Italian stimuli in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Note that it might not be possible to distinguish between serial and parallel models because certainly there will be a length effect in the duration of the response, but we will not know if it is due to computation of the orthographic code or the implementation of the motor code. We note that with Italian words that varied from five letters and two syllables to nine letters and four syllables, Cerni and Job (2022) found that response execution in both handwriting and typing began especially early for the longer items.…”
Section: Orthographic Lengthmentioning
confidence: 57%
See 1 more Smart Citation
“…Note that it might not be possible to distinguish between serial and parallel models because certainly there will be a length effect in the duration of the response, but we will not know if it is due to computation of the orthographic code or the implementation of the motor code. We note that with Italian words that varied from five letters and two syllables to nine letters and four syllables, Cerni and Job (2022) found that response execution in both handwriting and typing began especially early for the longer items.…”
Section: Orthographic Lengthmentioning
confidence: 57%
“…Perhaps more interesting is the evidence that the written response appears to cascade over time such that the processing of central lexical access and graphemic construction processes may not be fully complete when the execution of the peripheral motor response (i.e., of typing or writing) commences. This highlights the utility of collecting both measures of the response initiation as well as the duration of the spelling response over time (e.g., Cerni & Job, 2022;Roux et al, 2013) We note that our first key RT measures the time between the offset of the acoustic signal and the first keypress. This procedure differs from other spelling studies that measure RT from the onset of the acoustic signal (e.g., Bonin et al, 2015).…”
mentioning
confidence: 94%
“…Although there is evidence that linguistic factors can affect typing performance (see previous section), the question of serial versus cascaded processing has not been fully resolved. Indeed, a recent article examining handwriting and typing concluded: “For handwriting, the pattern of results was compatible with a cascaded flow of linguistic processing during written execution, while for typing, a more intertwined pattern of cascade and serial processing emerged” (Cerni & Job, 2022, p. 576). One potential explanation for this variability in results is that the morphological structure of a word might influence the impact of lexical information, especially of word frequency.…”
Section: Research Traditions and Theoretical Approaches Concerning Ty...mentioning
confidence: 99%
“…Latencies for the initial letter of the word are faster for high-frequency words than for lower-frequency words (Baus et al, 2013;Feldman et al, 2019;Inhoff, 1991;Pinet et al, 2016;Torrance et al, 2018). In contrast, although there has been some evidence suggesting that some latencies at noninitial positions are affected by word frequency (Gentner, 1983;Gentner et al, 1988), the majority of studies have found that word frequency did not influence typing latencies for noninitial letters (e.g., Baus et al, 2013;Bertram et al, 2015;Cerni & Job, 2022;Pinet et al, 2016). Thus, it appears that higher word frequency has a facilitatory effect at the word level (e.g., initiating the first letter) but does not affect the letter-output level (e.g., the latencies for the noninitial letter keystrokes) or is more difficult to detect at noninitial positions.…”
Section: Lexicality and Lexical Frequency Effects As Indicators Of Le...mentioning
confidence: 99%
See 1 more Smart Citation